Final report of Harvard Gulch flood control project, conduit intake - Ruff, J. F., author; Engineering Research Center, Colorado State University, publisher (Colorado State University. Libraries, 1965)
This report describes a hydraulic model study of the intake to the 12-foot diameter conduit for the Harvard Gulch Flood Control Project, Design of an intake to provide a discharge of about 2100 cfs at an upstream water surface elevation of 128.7, to limit the flow at elevations above 128.7, and to accelerate the water to the uniform flow velocity in the conduit for the large discharges was the primary object of this study. A discharge rating curve for the intake is provided in Fig. 12. Flow conditions through the transition were satisfactory for all discharges. An air went should be provided in the conduit at a distance of 40 feet to 80 feet downstream from the transition, The exact location to be determined from the general location of the intake in relation to Logan Street. Velocity profiles in the conduit indicate that no u usual conditions prevail. The model construction tests and conclusions and recommendations are described in this report.
CER65JFR62.
December 1965.
Prepared for Wright-McLaughlin Engineers.
Keywords: Flood control -- Colorado; Intakes (Hydraulic engineering); Hydraulic models